Mia Halls Decision Making Process in Her Comatose State in Gayle Formans If I Stay: A Psychoanalytic Study - Chindy Christine; Dewi Widyastuti (Universitas Sanata Dharma, 2017)
This undergraduate study discusses a novel written by Gayle Forman entitled If I Stay through the psychoanalytic study. The main character of the novel, Mia Hall, is in a comatose state after she gets an accident with her family. Her parents and her brother do not survive. In this unconscious state, she has to choose one of the two choices whether to stay or to leave. Her decision-making process, which the main character faces, inspires the researcher to study how Mia Halls unconsciousness is able to influence her decision making. The researcher formulates two problems for this study: (1) how the main character is described in the plot development of the story, and (2) how the decision-making process of the main character is seen in the story.The analysis produces some results and findings. The first finding is that the main characters traits are family-centered, enthusiastic, loving, and thoughtful. The second result is that the main characters decision making process is a descriptive model of decision making. The reason why she decides to stay in the world is influenced by her identity and the effects of her unconsciousness, in which she still has her grandparents as her family, her dream to become a cellist that she can pursue, and the people surrounding her whom she can share her affection for. Keywords: psychoanalytic study, comatose state, Gayle Forman